Perivascular Hedgehog responsive cells play a critical role in peripheral nerve regeneration via controlling angiogenesis. (December 2021) - Yamada, Yurie; Nihara, Jun; Trakanant, Supaluk; Kudo, Takehisa; Seo, Kenji; Iida, Izumi; Izumi, Kenji; Kurose, Masayuki; Shimomura, Yutaka; Terunuma, Miho; Maeda, Takeyasu; Ohazama, Atsushi
Highlights: Hedgehog responsive cells [Gli1(+) cells] exist in perineurium and endoneurium. Gli1(+) cells in endoneurium were classified as blood vessel associated or non-associated. Gli1(+) cells accumulate into the injury site along with endothelial cells after injury. Loss of Hh signal activity in Gli1(+)cells cause disorganized vascularization. Loss of Hh signal activity in Gli1(+)cells results in failure of axonal regeneration. Abstract: Hh signaling has been shown to be activated in intact and injured peripheral nerve. However, the role of Hh signaling in peripheral nerve is not fully understood. In the present study, we observed that Hh signaling responsive cells [Gli1(+) cells] in both the perineurium and endoneurium. In the endoneurium, Gli1(+) cells were classified as blood vessel associated or non-associated. After injury, Gli1(+) cells around blood vessels mainly proliferated to then accumulate into the injury site along with endothelial cells. Hh signaling activity was retained in Gli1(+) cells during nerve regeneration. To understand the role of Hedgehog signaling in Gli1(+) cells during nerve regeneration, we examined mice with Gli1(+) cells-specific inactivation of Hh signaling ( Smo cKO ). After injury, Smo cKO mice showed significantly reduced numbers of accumulated Gli1(+) cells along with disorganized vascularization at an early stage of nerve regeneration, which subsequently led to an abnormal extension of the axon. Thus, Hh signaling in Gli1(+) cells appears to be involved in nerve regeneration through controlling new blood vessel formation at an early stage.